Biochemical basis for the formation of organ-specific volatile blends in mint - Lange, B. Markus; Srividya, Narayanan; Lange, Iris; Parrish, Amber N.; Benzenberg, Lukas R.; Pandelova, Iovanna; Vining, Kelly J.; Wüst, Matthias (Frontiers in Plant Science, 2023)
Above-ground material of members of the mint family is commercially distilled to extract essential oils, which are then formulated into a myriad of consumer products. Most of the research aimed at characterizing the processes involved in the formation of terpenoid oil constituents has focused on leaves. We now demonstrate, by investigating three mint species, peppermint (Mentha ˣ piperita L.), spearmint (Mentha spicata L.) and horsemint (Mentha longifolia (L.) Huds.; accessions CMEN 585 and CMEN 584), that other organs – namely stems, rhizomes and roots – also emit volatiles and that the terpenoid volatile composition of these organs can vary substantially from that of leaves, supporting the notion that substantial, currently underappreciated, chemical diversity exists. Differences in volatile quantities released by plants whose roots had been dipped in a V. dahliae-spore suspension (experimental) or dipped in water (controls) were evident: increases of some volatiles in the root headspace of mint species that are susceptible to Verticillium wilt disease (peppermint and M. longifolia CMEN 584) were detected, while the quantities of certain volatiles decreased in rhizomes of species that show resistance to the disease (spearmint and M. longifolia CMEN 585). To address the genetic and biochemical basis underlying chemical diversity, we took advantage of the newly sequenced M. longifolia CMEN 585 genome to identify candidate genes putatively coding for monoterpene synthases (MTSs), the enzymes that catalyze the first committed step in the biosynthesis of monoterpenoid volatiles. The functions of these genes were established by heterologous expression in Escherichia coli, purification of the corresponding recombinant proteins, and enzyme assays, thereby establishing the existence of MTSs with activities to convert a common substrate, geranyl diphosphate, to (+)-α-terpineol, 1,8- cineole, γ-terpinene, and (–)-bornyl diphosphate, but were not active with other potential substrates. In conjunction with previously described MTSs that catalyze the formation of (–)-β-pinene and (–)-limonene, the product profiles of the MTSs identified here can explain the generation of all major monoterpene skeletons represented in the volatiles released by different mint organs.